Proyectos identitarios en la construcción del Museo Nacional de la Inmigración de Buenos Aires (Altre Modernità, 2011)
Visiting the National Immigration Museum is the occasion to think over the relation between a Country and its immigration history. Retrieving the memory of the transoceanic  migration to Argentina which characterized the last decades, is a process based upon the complex interconnection between the individual level and the general one; and whereas immigration as a mass phenomenon turns into an individual experience, the personal recollection is the tool that allows us to reconstruct the past social project and also to give shape to the existing National identity.Thus the Museum acts as safeguard for the immigration memory and at the same time for the political institutional legitimisation and it represents the promise of a prosperous future like the last decades did.